Enhanced photocatalytic performance of vertically grown ZnO nanorods decorated with metals (Al, Ag, Au, and Au–Pd) for degradation of industrial dye. (4th May 2017) - Chauhan, Pankaj Singh; Rai, Ashutosh; Gupta, Ankur; Bhattacharya, Shantanu
Abstract: In this work we have fabricated vertically grown novel rod type nanostructures of zinc oxide on a silicon substrate which are decorated with metals (Al, Ag, Au, and Au–Pd) using sputtering technique. These structures have been utilized in remediation of industrial dyes through solar light photo-catalysis with enhanced efficacy. The obtained structures have been thoroughly characterized using x-ray diffraction (XRD), field-emission scanning electron microscope (FESEM), and Fourier transform infrared spectroscopy (FTIR) analysis etc. The decorating elements have been compared for the photo-catalytic performance relative to the pristine zinc oxide structures and they are found to act as electron sink for the electrons generated by redox reaction on the surface of the ZnO nanostructure. This is attributed as a main reason for increasing the photocatalytic yield by the decorated structures. Approximately 20–45 % (maximum in case of Au–Pd and minimum in case of Ag) enhancement in dye degradation (concentration basis) was achieved by decoration of metals in comparison with undecorated ZnO nanorod. A theoretical model comprising of governing equations associated with the mechanism of the catalysis process was developed for proper understanding of the experimental data.